A New Interpretation of the Expression in the Tale of Two Brothers - Orriols-Llonch, Marc (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
In the tale of Two Brothers , when Bata tells his brother Inpu the whole truth about what happened with his wife, he insults her by calling her , a hapax that has been interpreted in many ways. F. Servajean has proposed to translate the expression by vagin perturbé and associates this “perturbation” with menstruation. The translation is totally adequate, but, given the context in which it is found, it does not seem right to associate it with menstruation. Bata insults the wife of his brother because she has tried to be unfaithful, so it seems more consistent that the “perturbation” of the vagina is due to an act of adultery rather than because of the woman’s menstruation.